2020
DOI: 10.1038/s41419-020-03026-3
|View full text |Cite
|
Sign up to set email alerts
|

LINC01106 drives colorectal cancer growth and stemness through a positive feedback loop to regulate the Gli family factors

Abstract: Long non-coding RNAs (lncRNAs) are essential contributors to the progression of various human cancers. Long intergenic non-protein coding RNA 1106 is a member of lncRNAs family. Until now, the specific role of LINC01106 in CRC remains undefined. The aim the current study was to unveil the functions of LINC01106 and explore its potential molecular mechanism in CRC. Based on the data of online database GEPIA, we determined that LINC01106 was expressed at a high level in colon adenocarcinoma (COAD) tissues compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…LINC01567 (also known as LOCCS) is highly expressed in colon CSCs that express CD133+/CD166+/CD44+, and its inhibition suppresses the proliferation, migration, invasion and tumor xenografts of colon CSCs via sponging miR-93 [ 54 ]. Recently, linc01106 confers colon cancer proliferation, migration, and stemness via regulating the Gli family factors partly by sponging miR-449b-5p [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…LINC01567 (also known as LOCCS) is highly expressed in colon CSCs that express CD133+/CD166+/CD44+, and its inhibition suppresses the proliferation, migration, invasion and tumor xenografts of colon CSCs via sponging miR-93 [ 54 ]. Recently, linc01106 confers colon cancer proliferation, migration, and stemness via regulating the Gli family factors partly by sponging miR-449b-5p [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…LINC01106 has been reported to facilitate proliferation and migration of colorectal cancer cells. Further investigation reveals that LINC01106 located in the nuclear could recruit FUS protein to Gli1 and Gli2 promoters, hence activating Gli1 and Gli2 transcription and promoting colorectal cancer formation [ 151 ]. Nevertheless, lncRNA HHIP-AS1 [ 152 ] acts as a tumor suppressor in HCC progression, which is attributed to its positive regulation of Hhip mRNA stability in a HuR-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…These lncRNAs also relate to CRC prognosis. Guo et al [ 96 ] found that lncRNA1106 is highly expressed in colon adenocarcinoma and induces the proliferation, migration, and stem cell properties of CRC cells. Cytoplasmic lncRNA1106 can be used as miR-449b-5p sponge.…”
Section: Lncrnasmentioning
confidence: 99%